2015
DOI: 10.1111/apa.13219
|View full text |Cite
|
Sign up to set email alerts
|

Country‐based reference values and international comparisons of clitoral size in healthy Nigerian newborn infants

Abstract: The present results make it possible to evaluate clitoral size in Nigerian newborn baby girls in an objective way, to identify genital abnormalities and endocrine disorders. Based on this study, a clitoral length of more than 10 mm would be considered clitoromegaly in a newborn girl in Nigeria.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
32
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(36 citation statements)
references
References 11 publications
2
32
2
Order By: Relevance
“…More African data will be needed to clarify this. Our MCW of 4.21 ± 1.1 mm was similar to reports from Jarrett et al [19] and Yokoya et al [21] of 4.4 ± 0.89 mm and 4.4 ± 1.2 mm respectively. Oberfield et al [17] reported a relatively lower mean clitoral width (MCW) of 3.32 ± 0.78 mm in North American term newborns.…”
Section: Discussionsupporting
confidence: 92%
See 4 more Smart Citations
“…More African data will be needed to clarify this. Our MCW of 4.21 ± 1.1 mm was similar to reports from Jarrett et al [19] and Yokoya et al [21] of 4.4 ± 0.89 mm and 4.4 ± 1.2 mm respectively. Oberfield et al [17] reported a relatively lower mean clitoral width (MCW) of 3.32 ± 0.78 mm in North American term newborns.…”
Section: Discussionsupporting
confidence: 92%
“…Our MCL was also similar to that of other studies that involved preterms, including the 3.66 ± 0.13 mm reported by Riley and Rosenbloom [13] in black term and preterm newborns in United States. Mondal et al [20] also reported a comparable albeit slightly lower MCL of 3.1 ± 1.54 mm in India and Jarrett et al [19] reported a relatively higher MCL of 7.7 ± 1.37 mm in 244 term and preterm newborns in Nigeria.…”
Section: Discussionmentioning
confidence: 96%
See 3 more Smart Citations